Amazonian deforestation and global warming: Carbon stocks in vegetation replacing Brazil's Amazon forest - Fearnside, Philip Martin (Forest Ecology and Management, 1996)
Carbon stocks in vegetation replacing forest in Brazilian Amazonia affect net emissions of greenhouse gases from land-use change. A Markov matrix of annual transition probabilities was constructed to estimate landscape composition in 1990 and to project future changes, assuming behavior of farmers and ranchers remains unchanged. The estimated 1990 landscape was 5.4% farmland, 44.8% productive pasture, 2.2% degraded pasture, 2.1% 'young' (1970 or later) secondary forest derived from agriculture, 28.1% 'young' secondary forest derived from pasture, and 17.4% 'old' (pre-1970) secondary forest. The landscape would eventually approach an equilibrium of 4.0% farmland, 43.8% productive pasture, 5.2% degraded pasture, 2.0% secondary forest derived from agriculture, and 44.9% secondary forest derived from pasture. An insignificant amount is regenerated 'forest' (defined as secondary forest over 100 years old). Average total biomass (dry matter, including below-ground and dead components) was 43.5 t ha-1 in 1990 in the 410 × 103 km2 deforested by that year for uses other than hydroelectric dams. At equilibrium, average biomass would be 28.5 t ha-1 over all deforested areas (excluding dams). These biomass values are more than double those forming the basis of deforestation emission estimates currently used by the Intergovernmental Panel on Climate Change (IPCC). Although higher replacement landscape biomass decreases net emissions from deforestation, these estimates still imply large net releases. © 1996 Elsevier Science B.V. All rights reserved.
Keywords: Biomass Budget; Carbon Sequestration; Carbon Stock; Climatic Change; Deforestation; Deforestation Emission; Greenhouse Gas Emission; Land Use; Net Release; Secondary Forest Growth; Secondary Succession; Amazonas; Brazil, Amazonia